Release of soluble receptors for tumor necrosis factor (TNF) in relation to circulating TNF during experimental endotoxinemia. - Spinas, G A (1992)
Serial plasma samples from human volunteers obtained after intravenous administration of Escherichia coli endotoxin were analyzed for the presence of circulating soluble tumor necrosis factor receptors (sTNFR). A four- to fivefold increase of type A (p75) and type B (p55) sTNFR was observed 3 h after endotoxin challenge. Pretreatment of the volunteers with ibuprofen before the injection of endotoxin resulted in a slight increase (3.87 +/- 0.2 vs. 3.27 +/- 0.3 ng/ml) and temporal shift of sTNFR-A release concurrent to a marked augmentation of TNF levels (603 +/- 118 vs. 338 +/- 56 pg/ml) as compared to the group without ibuprofen pretreatment. There was a significant correlation between peak sTNFR-A levels and peak TNF levels in the individual probands (r = 0.52, P = 0.04). On the contrary, release kinetics and plasma concentrations of sTNFR-B were identical in both groups (7.38 +/- 0.69 vs. 7.44 +/- 0.33 ng/ml) and no correlation with individual TNF levels was observed. The amount of sTNFR liberated upon endotoxin challenge was not sufficient to block TNF-mediated cytotoxic effects. Our data indicate that the release in vivo of type A and type B sTNFR upon a short exposure to endotoxin is regulated differently.